Acute Renal Failure in Sarcoidosis: A Review of the Literature - Teresa Papalia; Rosita Greco; Agata Mollica; Renzo Bonofiglio (Archives of Clinical Nephrology - Peertechz Publications, 2016)
We report two cases of acute kidney failure (ARF) as the initial manifestation of sarcoidosis. Two patients were sent from their primary care physicians with hypercalcemia and progressive increase of serum creatinine. The renal biopsy revealed granulomatous interstitial nephritis (GIN). Both patients were started on Methylprednisolone pulse therapy, followed by administration of oral prednisolone and by a slow taper thereafter to a maintenance dose. The renal function has improved immediately in response to this therapy. Our cases demostrates thet GIN due to sarcoidosis, although a rare entity, can cause severe ARF and progressive ESRD. With early detection and appropriate therapy, the majority of patients will maintain adequate renal function. Therefore the diagnosis of renal sarcoidosis must be done quickly to prevent renal.